An experimental study of acoustic responses on the injection of supercritical CO2 into sandstones from the Otway Basin - Lebedev, Maxim; Pervukhina, M.; Mikhaltsevitch, Vassili; Dance, T.; Bilenko, Olga; Gurevich, Boris (Society of Exploration Geophysics, 2013)
Quantitative knowledge of the acoustic response of rock from an injection site on supercritical CO2 (scCO2) saturation is crucial for understanding the feasibility of time-lapse seismic monitoring of CO2 plume migration. A suite of shaley sandstones from the injection interval of the CRC-2 well, Otway Basin, Australia is tested to reveal the effects of supercritical CO2 injection on acoustic responses. CO2 is first injected into dry samples, flushed out with brine and then injected again into brine-saturated samples. Such a suite of experiments allows us to obtain acoustic velocities of the samples for a wide range of CO2/brine saturations from 0% to 100%. On injection of scCO2 into brine-saturated samples, the rocks exhibit a decrease of compressional velocities by about 7% with the increase of CO2 saturation from 0% to a maximum of about 50%. Anisotropy of the shaley sandstones from the Otway Basin must be taken into account as the difference in the velocities normal and parallel to bedding is comparable with the perturbation due to CO2 injection and the samples of different orientations exhibit transition from Gassmann-Hill to Gassmann-Wood bound at different scCO2 saturations. Changes of the dry samples before and after the CO2 injection (if any) are not traceable by acoustic methods.